Bionomics of Anopheles latens in Kapit, Sarawak, Malaysian Borneo in relation to the transmission of zoonotic simian malaria parasite Plasmodium knowlesi - Tan, C.H.; Vythilingam, I.; Matusop, A.; Chan, S.T.; Singh, B. (2008)
Background A large focus of human infections with Plasmodium knowlesi, a simian parasite naturally found in long-tailed and pig-tailed macaques was discovered in the Kapit Division of Sarawak, Malaysian Borneo. A study was initiated to identify the vectors of malaria, to elucidate where transmission is taking place and to understand the bionomics of the vectors in Kapit. Methods Three different ecological sites in the forest, farm and longhouse in the Kapit district were selected for the study. Mosquitoes were collected by human landing collection at all sites and at the forest also by monkey-baited-traps situated on three different levels. All mosquitoes were identified and salivary glands and midguts of anopheline mosquitoes were dissected to determine the presence of malaria parasites. Results and Discussions Over an 11-month period, a total of 2,504 Anopheles mosquitoes comprising 12 species were caught; 1,035 at the farm, 774 at the forest and 425 at the longhouse. Anopheles latens (62.3) and Anopheles watsonii (30.6) were the predominant species caught in the forested ecotypes, while in the farm Anopheles donaldi (49.9) and An. latens (35.6) predominated. In the long house, An. latens (29.6) and An. donaldi (22.8) were the major Anopheline species. However, An. latens was the only mosquito positive for sporozoites and it was found to be attracted to both human and monkey hosts. In monkey-baited net traps, it preferred to bite monkeys at the canopy level than at ground level. An. latens was found biting early as 18.00 hours. Conclusion Anopheles latens is the main vector for P. knowlesi malaria parasites in the Kapit District of Sarawak, Malaysian Borneo. The study underscores the relationship between ecology, abundance and bionomics of anopheline fauna. The simio-anthropophagic and acrodendrophilic behaviour of An. latens makes it an efficient vector for the transmission of P. knowlesi parasites to both human and monkey hosts. Go to: Background Malaria parasites in Peninsular Malaysian monkeys were first reported in 1908 1, but only gained prominence in the 1960's after the accidental discovery 2 that Plasmodium cynomolgi could be transmitted to humans via mosquito bites in the laboratory. This stimulated interest at a time when the Malaria Eradication Programme was initiated by the World Health Organization 3 and it was important to determine if malaria was a zoonosis. Therefore, extensive studies were carried out in Peninsular Malaysia to determine the distribution, prevalence and species of malaria parasites in monkeys and apes and the natural vectors of monkey malaria parasites 4-7. Instead of uncovering human cynomolgi malaria infections, Plasmodium knowlesi was the first simian malaria parasite found to be infecting humans in nature. The first case was reported in 1965 from the state of Pahang 8, Peninsular Malaysia, followed by a second case five years later acquired from Johore, Peninsular Malaysia 9. It was postulated that P. knowlesi could be transmitted from monkeys to man and laboratory studies proved that it was possible 10. However, a large scale study that was initiated in Pahang to investigate whether malaria was a zoonosis, by a group of American and local researchers based at the Institute for Medical Research in Kuala Lumpur, Peninsular Malaysia, concluded that simian malaria in humans was an extremely rare event 11,12. This was based on their studies in which they collected blood samples from more than 1,100 local residents, pooled the samples and injected them into rhesus monkeys and none of the monkeys contracted malaria. However, in 2004 a large focus of human P. knowlesi infection was reported in the Kapit Division of Sarawak 13. In that study 71.6% (101/141) of human malaria cases at Kapit Hospital which had been identified by microscopy as single Plasmodium malariae infections were actually P. knowlesi and other non-P. malariae species by nested polymerase chain reaction (PCR) assays. Plasmodium knowlesi is naturally found in long-tailed macaques (Macaca fascicularis), pig-tailed macaques (Macaca nemestrina) 14 and banded leaf monkeys (Presbytis malalophos) 15,16. Since transmission of this zoonotic parasite to humans is occurring in the Kapit Division of Sarawak, Malaysian Borneo, it is important to identify the vectors so that appropriate measures can be planned and initiated to control the spread of simian malaria in humans. Numerous studies on vectors of human malaria have been carried out in Sarawak 17-20 but none of these have been undertaken in the Kapit District of Sarawak. Several anopheline species incriminated or suspected to transmit monkey malaria parasites in Peninsular Malaysia, such as Anopheles latens, Anopheles balabacensis are also present in Sarawak 21. Hence, the vectorial status of the anopheline species present in the Kapit Division needs to be ascertained in order to determine if they are competent vectors of simian malaria parasites. Furthermore, the epidemiological data of P. knowlesi infection in humans revealed that infections occur primarily in adults and no clustering of cases occurred within communities that live in communal longhouses, which suggests transmission of P. knowlesi to humans occurred away from the vicinity of the longhouses 13. Thus the objectives of this study were to determine the vectors of P. knowlesi and other simian malaria parasites in the Kapit Division of Sarawak; and to study the dynamics of these vectors in different ecological sites in order to elucidate the most likely place where transmission was taking place. Preliminary results of this study were reported where An. latens was incriminated as the vector for P. knowlesi 22. Here detailed results of this eleven-month study on vectors of malaria and their bionomics in the Kapit district of Sarawak, Malaysian Borneo is presented.